STRATEGI PENATAAN KAWASAN MALIOBORO MENJADI KAWASAN PEDESTRIAN (Universitas Esa Unggul, 2016)
Walking is a sure thing to do every human being, it is supported with adequate pedestrian and supports the activities of its citizens in walking. Departing from this, many emerging shopping centers with the concept of pedestrian area. In many big cities in Indonesia, things like this happen. One of them is in Malioboro area. Since ancient times, this area is already famous as a shopping center that is arranged in a linear and has a pedestrian path that supports the activities of its citizens in the interaction of buying and selling. Currently, the area of Malioboro has turned into an increasingly crowded and irregular areas. Many street vendors, as well as motorized parking lot that took the pedestrian path. Research Methods used in this study using qualitative descriptive method of doing direct observation to the location of Malioboro to know, understand and directly identify the actual conditions that occur in the study area. With data analysis method using SWOT analysis that analyze strength (Strengths), weakness (Weakness), Opportunities (Opportunities), and threat (Treatment) from Malioboro Region. The result of this study is the discovery of several factors that inhibit the Malioboro Region into a pedestrian area. With the identification of these factors, then a strategy devised based on SWOT analysis has been done to make the area into a pedestrian area.Â Keywords: pedestrian, malioboro region, regions, strategy